2018
DOI: 10.3390/cancers10020032
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Cancer Resistance by Immunotherapy: Updated Clinical Impact and Safety of PD-1/PD-L1 Inhibitors

Abstract: Cancer therapy has been constantly evolving with the hope of finding the most effective agents with the least toxic effects to eradicate tumors. Cancer immunotherapy is currently among the most promising options, fulfilling this hope in a wide range of tumors. Immunotherapy aims to activate immunity to fight cancer in a very specific and targeted manner; however, some abnormal immune reactions known as immune-related adverse events (IRAEs) might occur. Therefore, many researchers are aiming to define the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 93 publications
(109 reference statements)
1
38
0
Order By: Relevance
“…Echinococcus multilocularis proliferation and some malignant tumours are both sharing similar features such as local immune evasion, induction of tolerance and disruption of T cell signalling, and T cell exhaustion at late stage of infection . Monoclonal antibodies targeting PD‐1 or PD‐L1 are in clinical use demonstrating high efficacy in lung, colon, head, neck and gastric cancers, in addition to renal cell carcinoma and melanoma …”
Section: Introductionmentioning
confidence: 99%
“…Echinococcus multilocularis proliferation and some malignant tumours are both sharing similar features such as local immune evasion, induction of tolerance and disruption of T cell signalling, and T cell exhaustion at late stage of infection . Monoclonal antibodies targeting PD‐1 or PD‐L1 are in clinical use demonstrating high efficacy in lung, colon, head, neck and gastric cancers, in addition to renal cell carcinoma and melanoma …”
Section: Introductionmentioning
confidence: 99%
“…For example, the overall response rate to treatment with anti-PD-1 immune checkpoint inhibitors pembrolizumab or avelumab monotherapy in patients with triple-negative breast cancer that is positive for PD-L1 is 18.5% (n = 27) and 44.4% (n = 9) [12]. Also, the cost of immunotherapeutic agents is higher than the other conventional therapies, and their use is associated with the development of some immune-related adverse effects [15]. Therefore, finding efficient biomarkers that aid in optimal patient selection is still on the top-ranked research concerns that are extensively studied.…”
Section: Conclusion and Future Recommendationsmentioning
confidence: 99%
“…Until now, there are no approved therapeutic agents that specifically target PD-L2. In many clinical trials, PD-1/PD-L1 inhibitors showed superior efficacy and safety compared to the traditional chemotherapeutic agents [14,15]. However, the low response rates and the development of resistance are still among the major challenges encountered by this class of anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…However, although these methods have greatly increased the lifespan of many patients with malignant neoplasms, many patients with common cancer types do not respond to this treatment. Besides, inhibition of immune checkpoints causes multiple side effects, mostly autoimmune inflammatory reactions termed immune‐related adverse events …”
Section: Brief Summary Of Immune Checkpointsmentioning
confidence: 99%